2014
DOI: 10.2174/1568009614666140310120107
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Systemic Therapy in Ovarian Cancer

Abstract: Epithelial ovarian cancer (EOC) is the most deadly tumor of the female reproductive system. Despite improvements in understanding the biology of EOC, therapeutic strategies still depend on surgery and combination of taxane and platinum agents. Here, we provide a summary of clinically tested biomarkers potentially useful to predict drug response. Resistance against platinum derivatives can result from lower drug concentrations, alterations in the target molecule and changes in the cellular signal transduction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 135 publications
0
4
0
Order By: Relevance
“…The variability of biomarkers pre-treatment and percent change levels, both in mice and humans, indicate the usefulness of a panel of biomarkers for characterization. Biomarker panels would allow for an easier and more robust characterization of metastatic as well as primary lesions as is the consensus for the detection and management of disease [ 15 17 , 19 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variability of biomarkers pre-treatment and percent change levels, both in mice and humans, indicate the usefulness of a panel of biomarkers for characterization. Biomarker panels would allow for an easier and more robust characterization of metastatic as well as primary lesions as is the consensus for the detection and management of disease [ 15 17 , 19 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical environment of blood-based biomarker studies it has been shown that a single biomarker is generally not effective in detecting or guiding management and detection of disease, and that panels of multiple biomarkers are required [ 15 19 ]. Protein blood biomarkers such as carcinoembryonic antigen (CEA), cancer antigen 19–9 (CA19-9) and prostate specific antigen (PSA) used in this study, have been widely studied for many decades and are used in mainstream clinical disease management [ 20 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…To deliver personalized treatment decisions, a clear understanding of the exact mechanisms of drug resistance is required; resistance can be caused by multiple independent mechanisms, some of which have been extensively studied in patient samples and cell culture model systems. We and others have shown previously that resistance mechanisms against platinum-based agents include decreased drug accumulation [6], drug inactivation by glutathione and glutathione Stransferases [7], increased autophagy [8], and increased levels of DNA repair [9]. Taxane resistance can result from overexpressed efflux pump genes [10], modulated microtubule dynamics [11], altered expression of β tubulin isotypes [11] and enhanced epithelial-tomesenchymal transition [12].…”
Section: Introductionmentioning
confidence: 99%
“…Chemoresistance in ovarian cancer develops in response to alterations in intracellular drug concentration (increased sequestration, increased efflux), DNA repair/cell cycle regulation and/or intracellular signaling (5). In taxane-treated tumors, resistance may also result from alterations in microtubule structure (6). Whole-genome sequencing studies of primary high-grade serous carcinomas (93% of whom were treated with taxane-containing therapy) and matched tumor cells from recurrent ascites samples demonstrate a higher mutational burden in the recurrent samples compared to the primary tumors (7).…”
Section: Introductionmentioning
confidence: 99%